"Constitutional dismemberment" and the problem of pragmatism in Siddiqui: A reply to Po Jen Yap and Rehan Abeyratne. (6th October 2022) - Sayeed, M A; Aktar, Lima
Abstract: In their provocative article, Po Jen Yap and Rehan Abeyratne offer a theoretical and pragmatic defense of a somewhat "troubling decision" of the Bangladesh Supreme Court in Asaduzzaman Siddiqui. This article provides some critical remarks on the authors' evaluation of Siddiqui in both theoretical and pragmatic terms. In order to do this, we seek to advance two lines of argument. First, we note that, in offering theoretical justification, the authors have made a problematic choice of using two seemingly irreconcilable ideas—the idea of dismemberment and the basic structure doctrine. While using these two ideas in tandem, they did not remain, in our view, entirely true to the promise of either of them. Second, we argue that, although the authors' defense of Siddiqui on pragmatic grounds seems to be revealing, its legitimacy can, however, be questioned, insofar as Siddiqui's recourse to the Fifteenth Amendment shows contradictory appropriation itself of pragmatism in its own reasoning.